anonymous
  • anonymous
Solve for the indicated variable;A c squared = a squared + b squared
Mathematics
jamiebookeater
  • jamiebookeater
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

anonymous
  • anonymous
a squared =c squared - b squared
anonymous
  • anonymous
what?? im still confused. The problem is C squared = A squared + B squared and you need to solve for A... If you know how to do it can you explain to me again??? thx
anonymous
  • anonymous
if you want solve for a square you move square b to the left and change the side

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
do you subtract B squared and make it so its c squared minus b squared = a squared??? then from there what do you do????
anonymous
  • anonymous
c^2=a^2+b^2 a^2 = c ^2-b^2 a= √(c^2-b^2)
anonymous
  • anonymous
on the second step... can you explain that 2 me really fast... i dont understand how u got from the first step 2 the second...
anonymous
  • anonymous
let use the number: 2=3, b=4 c^2=a^2+b^2 =3^2+4^2 c^2=25 c= √(25) c=5 Solve for a 3^2=5^2-4^2 9=25-16 9=9 Are you understand now?
anonymous
  • anonymous
sory my keyboard not work properly let use the number: a=3, b=4 c^2=a^2+b^2 =3^2+4^2 c^2=25 c= √(25) c=5 Solve for a 3^2=5^2-4^2 9=25-16 9=9 Are you understand now?

Looking for something else?

Not the answer you are looking for? Search for more explanations.